Effects of seedling thickness on the production and quality of onion (Allium cepa L.) ‘Santa Rita’ in Arequipa, Peru - Almeyda Carbajal, Diego (2021)
Onion crop begins with seedling preparation and finishes with transplanting. In some Peruvian onion-productive areas, it is assumed that seedling thickness is important to have a better yield. Four different seedling thickness of red onion (Allium cepa L.) were evaluated between February and June 2017 in Santa Rita de Siguas, Arequipa, Peru. The seedling thicknesses evaluated were very thin (2.00 mm – 3.49 mm), thin (3.50 mm – 4.99 mm), standard (5.00 mm – 6.49 mm) and thick (6.50 mm – 7.99 mm). The plant density was 340 000 plants ha−1. The experimental design was a randomized complete block with four treatments and five replications. The variables evaluated were plant height (cm), leaf number, stemlike diameter (mm), bulb diameter (mm), total yield (t ha−1), and marketable yield categories (t ha−1). The leaf number, plant height, and stemlike diameter among treatments were significantly different, with higher values in the “standard” and “thick” treatments up to 60 days after transplanting. The harvest was earlier in the “standard” and “thick” treatments. The “very thin” and “thin” treatments needed more days to harvest than the others. The “thin” treatment showed the highest total yield. There were no significant differences between marketable yield categories in all treatments. It was concluded that seedling thickness upon transplanting influences the yield under the conditions in this study.